Effect Of Dietary Supplementation Of L-Carnitine On Serum Lipid Profile And Antioxidant Status In Broiler Chicken Fed With Animal Fat-Rich Diet (Applied Biological Research, 2020)
A study was conducted to evaluate the effects of L-carnitine  supplementation on serum lipid profile and antioxidant status of broilers  fed with animal fat-based diet. Eighty days old straight run commercial  broiler chicks (Vencobb) were randomly grouped into two treatment groups  with four replications of ten chicks each. The rations were prepared with  5% animal fat. One group was supplemented with 900 mg L-carnitine kg-1 feed. The L-carnitine supplementation significantly reduced the serum  cholesterol and LDL cholesterol levels; whereas serum triglyceride, HDL cholesterol and VLDL-cholesterol levels didn’t show any significant  changes. The serum reduced-glutathione and superoxide dismutase  concentrations were significantly higher in L-carnitine supplemented  group. The study revealed that the supplementation of L carnitine not only  improves the immune status but also decreases the serum cholesterol and  LDL cholesterol level in broiler birds.
Keywords: Broiler chicks; L-carnitine; reduced glutathione; serum cholesterol; superoxide dismutase